Pharmacokinetics, Tissue Residues, and Withdrawal Times of Oxytetracycline in Rainbow Trout (Oncorhynchus mykiss) after Single- and Multiple-Dose Oral Administration - Corum, Orhan; Durna Corum, Duygu; Terzi, Ertugrul; Uney, Kamil (MDPI AG, 2023)
The aim of this study was to compare the pharmacokinetics of oxytetracycline (OTC) following single- (60 mg/kg) and multiple-dose oral administrations (60 mg/kg, every 24 h for 7 days) in rainbow trout. It also aimed to determine bioavailability after a single dose and tissue residues and withdrawal times after multiple doses. This study was carried out on 420 rainbow trout at 9 ± 0.8 °C. This study was carried out in two stages: single-dose (intravascular and oral) and multiple-dose treatment. The OTC concentrations in plasma and tissues were measured by high-performance liquid chromatography and analyzed by a non-compartmental method. The withdrawal time (WT) was estimated using the WT 1.4 software. OTC exhibited a long terminal elimination half-life (t1/2ʎz) after IV and oral administration. The oral bioavailability of OTC was very low (2.80%). In multiple-dose treatment, t1/2ʎz, the area under the plasma concentration–time curve and peak plasma concentration increased significantly after the last day compared to the first day. OTC showed strong accumulation after multiple doses with a value of 5.33. OTC concentrations were obtained in the order liver > kidney > muscle+skin > plasma. At 9 ± 0.8 °C, the WT calculated for muscle+skin was 56 days for Europe and 50 days for China, respectively. The t1/2ʎz (68.94 h) and time (68 h) above the 1 µg/mL MIC following a single OTC dose may support the extension of the 24 h dosing interval following multiple dosing. However, further studies are required to determine the optimal dosage regimen in multiple-dose OTC treatment in the treatment of infections caused by susceptible pathogens.
Keywords: food safety; aquaculture; QL1-991; Veterinary medicine; public health; SF600-1100; drug residue; Zoology; antibiotics; Article; 3. Good health